Methodist Missionary Society archives, London, [on microfiche] ([IDC microedition] ;, 1982)
Methodist missionary correspondence chiefly from Transvaal (1881-1947); includes some correspondence from Swaziland (ca. 1881-1884) and Portuguese East Africa (ca. 1927-1930)